Optimization of Magneto-Rheological Fluids on the volume fraction and viscosity for MR damper application - Siti Aishah, Wahid; Izwan, Ismail (Indonesian Institute for Counseling, Education and Theraphy (iiCET), 2020)
Magneto-rheological fluid (MR fluid) in squeeze mode able to produce stress resistance up to 80kPa which is exceeded most basic requirement of normal mechanical application. However, to attain the good performance of stress resistance, the composition of MR fluids has to be optimized. The aim of this study is to investigate the optimum volume fraction of carbonyl iron particle (CIP), mineral oil (MO) and fumed silica (FS) for MR damper application. Simultaneously, the appropriate viscosity of MO is also studied. Hence, MR fluid samples with various composition are synthesized and analysed according to combined D-Optimal mixture design (CDMD) design of experiment (DOE). The compression test was conducted to study the compression strength and compression modulus of each samples. The findings indicate that the volume fraction of CIP is the most significant factor to affect the compression stress and compression modulus of MR fluid. Increment of CIP volume fraction from 20vol% to 40vol% increased the compression stress from 0.12MPa to 10.95MPa. Moreover, the compression modulus increased from 0.24MPa to 27.24MPa. This study shows that MR fluid can be produced for MR damper by selecting higher magnetic particles composition. Optimization model produced in this study is crucial for composing aimed squeeze mode MR fluid for MR damper.